Evaluation of Severity of Illness Scores in the Pediatric ECMO Population - Pinto, Venessa L.; Guffey, Danielle; Loftis, Laura; Bembea, Melania M.; Spinella, Philip C.; Hanson, Sheila J. (Frontiers in Pediatrics, 2021)
Though commonly used for adjustment of risk, severity of illness and mortality risk prediction scores, based on the first 24 hours of intensive care unit (ICU) admission, have not been validated in the pediatric extracorporeal membrane oxygenation (ECMO) population. We aimed to determine the association of Paediatric Index of Mortality 2 (PIM2), Pediatric Risk of Mortality Score III (PRISM III) and Paediatric Logistic Organ Dysfunction (PELOD) scores with mortality in pediatric patients on ECMO. This was a retrospective cohort study of children ≤18 years of age included in the Pediatric ECMO Outcomes Registry (PEDECOR) from 2014 to 2018. Logistic regression and Receiver Operating Characteristics (ROC) curves were used to calculate the area under the curve (AUC) to evaluate association of mortality with the scores. Of the 655 cases, 289 (44.1%) did not survive until hospital discharge. AUCs for PIM2, PRISM III, and PELOD predicting mortality were 0.52, 0.52, and 0.51 respectively. PIM2, PRISM III, and PELOD scores are not associated with odds of mortality for pediatric patients receiving ECMO. These scores for a general pediatric ICU population should not be used for prognostication or risk stratification of a select population such as ECMO patients.